Introduktion till postkvalitativ metodologi - Gunnarsson, Karin (Stockholm Studies in Education, 2021)
This book is an introduction to postqualitative methodology. It situates postqualitative methodology in feminist and posthumanist theories, where research is a worlding practice. Through addressing the relationality of inquiry, the book considers knowledge production as both material and discursive and proposes experimenting with research practices. Rather than offering instructions on how to conduct research, the book invites the reader to explore questions on how to form research problems, address research ethics and construct and analyze empirical material. By focusing on methodological as well as theoretical elaborations it can be inspirational within a range of different research areas, and work as a companion both for students and researchers.